2005
DOI: 10.1007/s11104-005-1153-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Douglas-fir and Scots pine seedlings on plagioclase weathering under acidic conditions

Abstract: The weathering of soil minerals in forest ecosystems increases nutrient availability for the trees. The rate of such weathering and its relative contribution to forest tree nutrition, is a major issue when evaluating present and potential forest stand productivity and sustainability. The current paper examines the weathering rate of plagioclase with and without Douglas-fir or Scots pine seedlings, in a laboratory experiment at pH 3-4 and 25 • C. All nutrients, with the exception of Ca, were supplied in suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 42 publications
2
15
0
1
Order By: Relevance
“…Our results are in accordance with those of Bormann et al (10), who demonstrated in an experimental forest that red pine (Pinus resinosa) plants improved by factors of 2.4 and 1.8 the quantities of calcium and magnesium released by weathering the primary minerals in a forest soil, respectively. In the same way, our results are in accordance with those of Bakker et al (4), who measured plagioclase weathering in a laboratory experiment at pH 3 to 4 and 25°C and showed that the release of Si, Mg, Ca, and Al was increased by a factor of 1.8 in the presence of Douglas fir and Scots pine under these acidic conditions. This effect of plant roots on mineral weathering may result from physical and/or biochemical processes.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with those of Bormann et al (10), who demonstrated in an experimental forest that red pine (Pinus resinosa) plants improved by factors of 2.4 and 1.8 the quantities of calcium and magnesium released by weathering the primary minerals in a forest soil, respectively. In the same way, our results are in accordance with those of Bakker et al (4), who measured plagioclase weathering in a laboratory experiment at pH 3 to 4 and 25°C and showed that the release of Si, Mg, Ca, and Al was increased by a factor of 1.8 in the presence of Douglas fir and Scots pine under these acidic conditions. This effect of plant roots on mineral weathering may result from physical and/or biochemical processes.…”
Section: Discussionsupporting
confidence: 93%
“…These workers also noted a significant increase in the number of lateral roots and root hairs and promoted growth of pine. Bakker et al (2004) opined that the following changes could promote the effect of K solubilization from minerals: (i) the fragmentation of the minerals due to root activity with a consequent increase in their reactive surfaces, (ii) the root exudates provide the substrates for the bacteria to produce metabolites, (iii) and the production of growth hormones by the bacteria and organic acids to stimulate root development and more root exudation, to effect weathering of K mineral and removal of nutrients by plant uptake (Gahoonia et al 1997). …”
Section: +mentioning
confidence: 99%
“…In terms of mineral weathering, the rhizosphere thus ends up being an environment more corrosive to mineral structures than that of the adjacent bulk soil. This action has been demonstrated in various studies (Leyval and Berthelin, 1991;Hinsinger et al, 1992;Arocena and Glowa, 2000;Bakker et al, 2004) for weatherable minerals such as micas, apatite, and amphiboles. Hence, the dissolution of soil solids triggered by acidification of the rhizosphere increases the mobilization of metals and their uptake by plants (Marschner, 1995), as demonstrated by Loosemore et al (2004) for tobacco (Nicotiana tabacum L. cv.…”
Section: Gradients In Solid-phase Metals and Metalloidsmentioning
confidence: 76%
“…The rhizosphere has been variously conceptualized as the soil-root interface , the environment of plant roots (Lorenz et al, 1997), the portion of the soil in contact with or adhering to roots (Pierret et al, 1999), the zone where root activity significantly influences soil biological properties , the soil in which the microbial activity is influenced by plant roots (Russell, 1982), and the soil volume surrounding roots and containing high densities of microbionts (Bakker et al, 2004). In this context, the rhizosphere is probably best defined as the volume of soil surrounding living plant roots and that is influenced by root activity (Hinsinger, 1998;Hinsinger et al, 2005).…”
Section: Rhizospherementioning
confidence: 99%